Promosi Kesehatan Melalui Buku Saku Higiene Menstruasi pada Situasi Bencana Meningkatkan Pengetahuan Remaja Putri di Desa Bangga Sigi - Batjo, Siti Hadijah; Taqwin; Rindi, Anak Agung (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Bangga Village, Sigi Regency, Central Sulawesi is one of the villages that experienced flash floods. The impact is the problem of female reproductive health. The aim of the study was to determine the effectiveness of health promotion using the menstrual hygiene pocket book in disaster situations on the knowledge of young women. This type of research is a pre-experimental design with one group pre-test and post-test. The research was conducted at the Youth Posyandu in June-July 2022. The study population was all young women aged 14-17 years in Bangga Village, Sigi Regency, Central Sulawesi. The sampling technique is purposive. The sample size is 27 respondents. The research questionnaire consisted of 20 questions. Questionnaire measurements were carried out through pre-test and post-test on the same day. The statistical test used is Wilcoxon. The results of the study showed that the respondents' knowledge was lacking 3 (11%), 24 (89%) sufficient and 0 (0%) good. Knowledge of post respondents who lacked 0 (0%), enough 4 (15%) and good 23 (85%). The Wilcoxon test results obtained ρ-value = 0.000 (<0.05). The conclusion of health promotion using pocket books on menstrual hygiene in disaster situations increases the knowledge of young women in Youth Posyandu. It is hoped that there will be more menstrual hygiene pocket books in disaster situations and distributed to young women.